Effect of evaporative cooling on heat stress mitigation and activity behavior in high-yielding dairy cows - Severino Pinto; Alisa Sergeeva; Christian Ammon; Vitaly Belik; Thomas Amon; Gundula Hoffmann (agricultural engineering.eu)
The present study aimed to evaluate the heat mitigation from evaporative cooling on the respiration rate (RR) and activity behavior in dairy cows under hot and dry climate in Mediterranean conditions. Twelve multiparous high-yielding Holstein dairy cows (2nd to 5th lactation) were randomly selected. Each cow was equipped with one pedometer to monitor different activity traits related to “resting” and “locomotion” behavior. The ambient temperature (AT) and relative humidity (RH) were recorded and the temperature-humidity index (THI) was calculated. A linear mixed model with repeated measurements was established to test the THI influence and cooling effect on animal traits. The RR regarding the second cooling decreased (54.6 ± 10.7) compared to the responses of cows an hour before (74.6 ± 13.1 breaths per min (bpm); p < 0.001). The lying behavior tended to increase after the cooling sessions, especially post-evening cooling (39 ± 4.76 bpm; p < 0.001). The evaporative cooling promoted a heat stress abatement by RR values and lying time behavior in dairy cows under hot and dry climate conditions.